Predictors of sick leave days in patients affected by major depressive disorder receiving antidepressant treatment in general practice setting in Germany. (2nd November 2021) - Kasper, Siegfried; Bonelli, Annalisa; Cattaneo, Agnese; Comandini, Alessandro; Di Dato, Giorgio; Heiman, Franca; Pegoraro, Valeria; Palao, Diego; Roca, Miquel; Volz, Hans-Peter
Abstract: Objective: To identify sick leave days (SLD) predictors after starting antidepressant (AD) treatment in patients affected by major depressive disorder (MDD), managed by general practitioners, with a focus on different AD therapeutic approaches. Methods: Retrospective study on German IQVIA ® Disease Analyser database. 19–64 year old MDD patients initiating AD treatment between July-2016 and June-2018 were grouped by therapeutic approach (AD monotherapy versus combination/switch/add-on). Data were analysed descriptively by AD therapeutic approach, while a zero-inflated Poisson (ZIP) multiple regression model was run to evaluate SLD predictors. Results: 8, 891 patients met inclusion criteria (monotherapy: 66%; combination/switch/add-on: 34%). All covariates had an influence on SLD after AD treatment initiation. Focussing on variables that physicians may more easily intervene to improve outcomes, it was found that the expected SLD number of combination/switch/add-on patients was 1.6 times that of monotherapy patients, and the expected SLD number of patients diagnosed with MDD before the decision to start AD treatment was 1.2 times that of patients not diagnosed with MDD. Conclusions: A patient tailored approach in the selection of AD treatment at the time of MDD diagnosis may improve functional recovery and help to reduce the socio-economic burden of the disease. KEY POINTS: Few studies previously investigated the effect of antidepressant treatment approaches on sick leave days in major depressive disorder. To the authors' knowledge, this is the first study evaluating the effect of different antidepressant treatment approaches on sick leave days in major depressive disorder in German patients. Patients receiving antidepressant monotherapy treatment seemed to lose fewer working days than patients receiving antidepressants combination/switch/add-on therapy, both before and after starting treatment, even if differences were more pronounced after treatment has started. The use of antidepressant monotherapy or combination/switch/add-on therapy was the strongest predictor of sick leave days after starting antidepressant treatment: the expected number of sick leave days for the combination/switch/add-on group was 1.6 times that of the monotherapy group. Among factors associated with increased sick leave days, antidepressant therapeutic approach and the promptness of starting the antidepressant treatment when major depressive disorder is diagnosed, are those on which physicians may more easily intervene to improve outcomes. Findings from the present study suggest that a patient tailored approach may improve functional recovery and help reducing the socio-economic burden of the disease.